Developing awareness of the national heritage and some values of citizenship among the kindergarten Child In light of the National Standards Document for Kindergarten - Randa El - Deeb (International Journal of Instructional Technology and Educational Studies)
Developing the concept of citizenship for the child, including the rights and duties it includes, is a positive way to create a good, effective citizen in society.For this reason, it was observed through field visits to some kindergartens that the children do not have awareness of the national heritage and the values ​​of citizenship, and that most kindergarten teachers do not present the national heritage and the values ​​of citizenship with interest as the rest of the concepts are presented, and that everything that is presented to the child on this subject is their diligence and does not go beyond discussion with Children, although there is a field of historical concepts in the National Standards Document for Kindergarten, and it contains a set of indicators only, and there are no codified programs approved by the Ministry of Education that affect the field of historical concepts.The quasi-experimental approach was relied on with a one-group design with a tribal and remote application of the research tools, and the tools were applied over a period of two months to second-level kindergarten children aged (5-6) years in the Future Model Kindergarten in Tala city, Menoufia Governorate. The results proved the effectiveness of the program of activities and recommended the application of the program in the rest of the kindergartens.